Meningkatkan Aktivitas dan Hasil Belajar Membaca Pemahaman Siswa Menggunakan Model Pembelajaran ROBOT pada Pelajaran Bahasa Indonesia Materi Teks Nonfiksi di Kelas 5 SDN Simpang Empat Banjar - Muhammad Fadhil Hasani; Mahmuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research is the low level of activity, critical thinking skills and student learning outcomes. This is because the learning process still applies teacher centered learning, and students have difficulty understanding non-fiction text material in Indonesian language subjects. An effort to overcome this problem is by implementing the ROBOT learning model which is a combination of the Problem Based Learning, Cooperative Integrated Reading and Composition, and Talking Stick models. The aim of this research is to increase teacher activity, student activity and student learning outcomes. This research used Class Research (PTK) which was carried out in 4 meetings. The subjects of this research were class V students at SDN Simpang Empat, Kertak Hanyar District, Banjar Regency, totaling 24 students consisting of 15 male students and 9 female students, in semester 2 of the 2023/2024 academic year. This research uses a qualitative approach. The data taken is qualitative data obtained through observing teacher activities, student activities and then using quantitative data for student learning outcomes obtained through group and individual written tests. The results of this research show that the teacher's activity at meeting 4 received a score of 23 with the criteria